Effectiveness analysis of virtual practicum in basic physics course using PhET simulation - Muflihah, Nur; Farida, Fatma Ayu Nuning; S, Sumasrono (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2023)
In order for the practicum to still be carried out, alternative practicum learning media are needed. An interactive application based on research of physics phenomena is PhET (Physics Education Technology) simulation. This study aims to determine the level of effectiveness of virtual basic physics practicum and the level of student understanding of basic physics courses through virtual practicum with PhET simulation. Interactive learning and allowing students to practice independently, limited practicum equipment facilities and inadequate laboratory space are the main contributing factors. In order to compare the differences in student learning outcomes between experimental and control courses, this study used a Pre test-Post test Control Group Design with one experimental class or treatment class and one control class to test the difference in student learning outcomes between experimental and control classes using data processing procedures using the True Experiment method. Based on the research, the effectiveness of using PhET simulation application media has an N-gain value of 0.66 and can increase understanding of lecture material by 52%.